(untitled) (Pakistan Journal of Engineering, Technology and Science, 2024)
Bitcoin is the most successful cryptocurrency with the highest market capitalization of up to 53%. Due to its pseudonymous mechanism, bitcoin is being utilized in a variety of illicit activities. It is noticed, around US72 billions of unlawful activities per year involve Bitcoin. In this study, systematic literature review is conducted on the illicit use of bitcoin, and the measures required to counter the illicit activities using Bitcon. In this work, authors have managed to select 45 research articles published during 2018-2022. The synthesis of selected articles revealed that bitcoin is proliferating in darknet markets. It is used to make payments for criminal activities such as drug trafficking, money laundering, human trafficking, pornography, ransomware, and other criminal activities like contract killers, Ponzi schemes, and terrorism financing. By the findings from this study, out of45 research articles 24.4% articles claim that bitcoin has been used in drug trafficking whereas 17.7% believe that people use bitcoin for money laundering. Moreover, Blockchain identity flexibility, dissociative anonymity, and a lack of deterrence encourage users to perform illegal activities. At present, the research community is actively involved in proposing and designing innovative approaches tocounter the illicit use of bitcoin. However, these solutions are unable to stop the misuse of bitcoin.